แรงจูงใจของผู้บริโภคในอำเภอเมืองเชียงใหม่ต่อการสมัคร สมาชิกร้านค้าปลีกเสื้อผ้าสำเร็จรูป - ปรารถนา บูรพาไพศาล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This independent study aimed to explore the motivation of consumers in Mueang Chiang Mai district towards subscribing for the membership of clothes retail stores and to study their behavior in purchasing clothes. Population of this study included consumers who resided or worked in Mueang Chiang Mai district and were the membership of My Card, CMS or Minor Plus. Data were collected from 300 respondents by using questionnaires, then analyzed by descriptive statistics, consisting of frequency, percentage, and mean. The findings presented that the majority of respondents were female in the age of 30-39 years old, graduated in bachelor’s degree, worked as private company employee, and earned monthly income at 15,001-30,000 Baht. Frequency in purchasing clothes was every month and expense for clothes that they spent in each time of purchase was 1,001-3,000 Baht. Factors influencing their purchasing decision for clothes were pattern and design. The results of the study on motivations of the respondents in subscribing for the membership of cloth retail stores presented that the following needs were respectively ranked at agree level: physiological need, the need of being oneself, the need of safety, the self-esteem need, and the social need. Considering each class of motivation, the sub items that were rated at the highest average scores were as follows. Physiological need: Free subscription fee and membership cards never expire. Safety Needs: The Company brings some of the purchases to help the poor / disadvantaged. Social Needs: The brand of clothing member used to buy and wearing. Esteem needs: Receive exclusive discounts on major festivals or special occasions. Self-Actualization Needs: Get great bargains when buying a gift for someone in your family and friends.